2012
DOI: 10.1371/journal.pone.0041049
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Uterine Sarcoma Cell Growth through Suppression of Endogenous Tyrosine Kinase B Signaling

Abstract: Uterine leiomyosarcoma is an aggressive tumor typically found at advanced stages due to difficulties with early diagnosis. Because uterine leiomyosarcoma is resistant to conventional radiation and chemotherapy, the development of more potent medical therapeutics is anticipated. Using quantitative real-time RT-PCR and immunostaining, we found the expression of brain-derived neurotrophic factor (BDNF) and neurotropin-4/5, together with their receptor, tyrosine kinase B (TrkB), in different uterine sarcoma cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…Previous studies have demonstrated a key role for BDNF-TrkB signaling in modulating the response to cytotoxic agents, and modulation of TrkB expression enhanced the sensitivity of cells to cis-Diamminedichloroplatinum Cisplatin (CDDP) in head and neck squamous cell carcinoma [16]. Recently, It was reported Trk inhibitor K252a inhibited cell growth and induced apoptotic cell death in uterine leiomyosarcoma [47].Therefore, further studies are needed to explore the development of small-molecule compounds that act as TrkB antagonists, or monoclonal antibodies against either BDNF or TrkB, as promising novel therapies for the treatment of endometrial carcinoma. Our findings provide new insights into biological mechanisms of EC and establish TrkB as a potential target for future therapies for this disease.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated a key role for BDNF-TrkB signaling in modulating the response to cytotoxic agents, and modulation of TrkB expression enhanced the sensitivity of cells to cis-Diamminedichloroplatinum Cisplatin (CDDP) in head and neck squamous cell carcinoma [16]. Recently, It was reported Trk inhibitor K252a inhibited cell growth and induced apoptotic cell death in uterine leiomyosarcoma [47].Therefore, further studies are needed to explore the development of small-molecule compounds that act as TrkB antagonists, or monoclonal antibodies against either BDNF or TrkB, as promising novel therapies for the treatment of endometrial carcinoma. Our findings provide new insights into biological mechanisms of EC and establish TrkB as a potential target for future therapies for this disease.…”
Section: Discussionmentioning
confidence: 99%
“…Mice inoculated with breast cancer cells and treated with antibodies against BDNF display slower tumor progression compared to mice treated with control antibodies (38). These results were recapitulated in a mouse model of uterine sarcoma (39) and neuroblastoma (40,41). Mice flanked with choriocarcinoma xenografts and subsequently treated with K252a exhibited drastically slower tumor growth paralleled with a tumor-specific 15-fold increase in caspase-3/7 levels (42).…”
Section: Bdnf: a Governor Of Chemotherapeutic Sensitivitymentioning
confidence: 94%
“…injection of 6% chloral hydrate (0.6 mL/kg body weight), to prepare rat models of thoracic spinal cord transection (SI Materials and Methods). The amounts of k-252a and k-252b used in these experiments were based on previously published studies (26).…”
Section: Methodsmentioning
confidence: 99%